Regulatory T Cells Improved the Anti-cirrhosis Activity of Human Amniotic Mesenchymal Stem Cell in the Liver by Regulating the TGF-β-Indoleamine 2,3-Dioxygenase Signaling - Deng, Zhenhua; Zhou, Jinren; Mu, Xiaoxin; Gu, Jian; Li, Xiangyu; Shao, Qing; Li, Jinyang; Yang, Chao; Han, Guoyong; Zhao, Jie; Xia, Yongxiang (Frontiers in Cell and Developmental Biology, 2021)
Liver fibrosis is a progression stage of chronic liver disease, while current therapies can not cure or attune cirrhosis effectively. Human amniotic mesenchymal stromal cell (hAMSC) presented immunoregulatory and tissue repairability of multiple illnesses. Regulatory T cells (Treg) had been proved to be functional in reducing immune cell activity. We showed that co-infusion of hAMSC and Treg prevented mild liver fibrosis comparing with hAMSC or Treg alone group. In vitro study indicated that the addition of Treg or the supernatant of Treg improved the HGF secreting and cell differentiation ability of hAMSC. Reduction of TGF-β significantly decreased the HGF secreting and differentiation of hAMSC. Multiple signal neutralizers were added to the culture to understand further the mechanism, which showed that 1-MT, the suppressor of IDO, was involved in the effect of TGF-β in regulating hAMSC. Depletion of TGF-β or IDO signaling successfully abolished the effect of Treg in improving hAMSC’s function both in vitro and vivo. Finally, our result indicated that Treg improved the function of hAMSC by regulating the TGF-β-IDO signaling and co-infusion of hAMSC and Treg provided a promising approach for treating liver cirrhosis.